PDAM PMGS WEST BANDUNG OFFICE - Moch Riou Badar Tubanie (Sean Institute, 2022)
PDAM PMGS Office is a place where a clean water service that meets human survival by providing convenience and solutions to problems in drought in the west Bandung area with physical methods such as the use of gravity as a distribution of clean water in every housing in west Bandung, with the ease of managing an administration and operational manager who needs a container to trade without interruption and requires a special space to bias to do its activities well, how a design realizes it, by solving this problem requires clear analysis and data. PT Perdana Multiguna Sarana Bandung Barat or abbreviated as PMgS is a Regional Millk Business Entity (BUMD) owned by the West Bandung Regency Regional Government, and is the first BUMD in West Bandung Regency in accordance with West Bandung Regency Regional Regulation Number 21 of 2009 concerning the establishment of regionally owned bada nusaha (BUMD) PT Perdana Multiguna Sarana West Bandung. PMgS is a Holding Company where there will be many subsidiaries including: PDAM, Tourism, Energy, Agro Business. Trading.Infrastructure, etc. has a solid Business Model, which is biased towards embracing Global Trader.Tourist.& Investors, to jointly build West Bandung within the framework of a win-win situation. One of pt PMgS's business fields is drinking water management and remains in the Decree of the Regent of West Bandung number: 601/ Kep.354-DCKTR/2011 concerning the Determination of Raw Water Management Areas for The Provision of Drinking Water for Urban Communities in West Bandung Regency, there is also the establishment of PMgS aimed at helping to increase Regional Original Income in West Bandung Regency